Revitalizing Islamic Education: The Role of Management and Curriculum Design in Addressing Social Change in Pesantren - Luthfi Setya Rahmadani; Setya Raharja (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This study aims to examine how Islamic boarding schools (pesantren) manage and redesign their curricula to respond to the challenges of modernization and social change. The present study employs a qualitative research method of a phenomenological nature. This study was conducted at two educational institutions: the Pondok Pesantren Nurul Ummah Kotagede and the Pondok Pesantren Kotagede Hidayatul Mubtadi'ien (PPKHM). The informants in this study consist of the head of the Madrasah Diniyah, the deputy head of the curriculum department of the Madrasah Diniyah, and teachers at the Madrasah Diniyah. The data collection techniques employed in this study encompass in-depth interviews, non-participant observation, and document analysis. The data analysis techniques employed the phenomenological data analysis model of Moustakas through researcher reflexivity, textual description, structural description, and extracting the 'essence' of informants' experiences, which reveal